Evaluation Criteria for Interactive E-Books for Open and Distance Learning - Bozkurt, Aras; Bozkaya, Mujgan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The aim of this mixed method study is to identify evaluation criteria for interactive e-books. To find answers for the research questions of the study, both quantitative and qualitative data were collected through a four-round Delphi study with a panel consisting of 30 experts. After that, a total of 20 interactive e-books were examined with heuristic inquiry methodology. In the final phase, the results of the Delphi technique and the heuristic inquiry results were integrated. As a result, four themes, 15 dimensions, and 37 criteria were developed for interactive e-books. Lastly, the results and their implications are discussed in this paper and suggestions for further research are presented.